2011
DOI: 10.1111/j.1365-2486.2010.02259.x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of drought and predicted effects of climate change on fish growth in temperate Australian lakes

Abstract: Climate change is expected to negatively impact many freshwater environments due to reductions in stream‐flow and increases in temperature. These conditions, however, can already be found today in areas experiencing significant drought; current observations of species' responses to droughts can be used to make predictions about their future responses to climate change. Using otolith analysis, we recreated golden perch (Macquaria ambigua) growth chronologies from two temperate lake populations in southeastern A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 47 publications
(63 reference statements)
1
64
1
Order By: Relevance
“…For example, the southerly range of golden perch (M. ambigua) is partly temperature-limited. Morrongiello et al (2011) found that during the recent drought, the annual growth of M. ambigua in south-eastern Australian lakes was negatively correlated with declining water levels; however, this effect was offset by increased growth during warmer years. Despite climatic models projecting significant declines in future water availability, fish growth may increase because of a disproportionate lengthening of the growing season, and thus make these higher latitudes more favourable habitat.…”
Section: South-eastern Australiamentioning
confidence: 93%
“…For example, the southerly range of golden perch (M. ambigua) is partly temperature-limited. Morrongiello et al (2011) found that during the recent drought, the annual growth of M. ambigua in south-eastern Australian lakes was negatively correlated with declining water levels; however, this effect was offset by increased growth during warmer years. Despite climatic models projecting significant declines in future water availability, fish growth may increase because of a disproportionate lengthening of the growing season, and thus make these higher latitudes more favourable habitat.…”
Section: South-eastern Australiamentioning
confidence: 93%
“…The effects of temperature on growth rates may also have indirect impacts by altering reproductive output and competitive interactions (e.g. Morrongiello et al 2011).…”
Section: Climate-change Drivers and Their Interactions With Fish Famentioning
confidence: 99%
“…Climate-change drivers such as temperature and rainfall can operate directly to affect range or indirectly through effects on habitat or food resources of fishes (e.g. Morrongiello et al 2011;Pratchett et al 2011) or on their reproduction (Pankhurst and Munday 2011). Climatechange drivers can also interact with other factors such as overfishing, habitat removal, disease and pollution to reduce or spatially shift species.…”
Section: Introductionmentioning
confidence: 99%
“…All models included the age at increment formation to account for the faster growth of younger fish (Morrongiello et al 2011). Annual otolith increment widths and ages were log transformed prior to analysis to achieve homoscedasticity and a linear relationship between these two variables.…”
Section: Sitementioning
confidence: 99%